Applied fluorescence in chemistry, biology, and medicine - Rettig, Wolfgang, 1947- (Springer, 1999)
This interdisciplinary book gives a comprehensive survey of the state-of-the-art and on trends in fluorescence techniques in science, medicine and engineering. The main chapters contain extended reviews which are supplemented by more specialized papers describing details and applications. The volume is intended for practitioners applying this technique in their routine work and for researchers in industry and academia, both groups being active in areas such as environmental monitoring, neuro and cell biology, molecular medicine, including gene research, microscopy and immuno-assays, physics, material science or chemsitry. Breathtaking new methods like ultra-fast time-resolved or single molecule spectroscopy and correlation techniques, fluorescence probes, or imaging techniques and their applications in the fields of electroluminescent polymers, visualization of membrane potentials in neurons or fluorescence imaging of the brain are described by internationally renowned authors.